2, 4‐dichlorophenoxyacetic acid induces ROS activation in NLRP3 inflammatory body‐induced autophagy disorder in microglia and the protective effect of Lycium barbarum polysaccharide. Issue 5 (31st January 2022) - Zhou, Jian; Wang, Faxuan; Jia, Leina; Chai, Ru; Wang, Hengquan; Wang, Xiaolan; Li, Jiangping; Wang, Kai; Zhang, Pengju; Yang, Huifang
Abstract: The pesticide 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) exerts neurotoxic effects; however, its action mechanism remains unclear. Here, we used BV2 cells as a model and divided them into six groups: control group (serum‐free medium), lipopolysaccharide (LPS) (1 μg/mL), 2, 4‐D (1.2 μmol/mL), Lycium barbarum polysaccharide (LBP; 300 μg/mL LBP), LPS (1 μg/mL) + LBP (300 μg/mL), and 2, 4‐D (1.2 μmol/mL) + LBP (300 μg/mL) with dimethyl sulfoxide as the solvent. Our results showed that 2, 4‐D treatment decreased superoxide dismutase and glutathione peroxidase activities and increased malondialdehyde content. The percentage of microglial activation (co‐expression of ionized calcium‐binding adaptor protein‐1 + CD68) in the LPS and 2, 4‐D groups and the levels of tumor necrosis factor alpha, interleukin (IL) 1 beta, IL‐6, and IL‐18 in the cell supernatant were increased. The protein and mRNA levels of Nod‐like receptor protein 3 (NLRP3), apoptosis‐associated speck‐like protein, caspase‐1, IL‐1β, IL‐18, and p62 increased, whereas those of LC3II/I and Beclin‐1 decreased in the 2, 4‐D group. The protein expression and mRNA levels of NLRP3, cleaved caspase‐1, IL‐1β, IL‐18, and p62 decreased significantly, whereas the protein expression and mRNA levels of LC3II/I and Beclin‐1 increased in small interfering RNA of NLRP3‐treated BV2 cells stimulated with 2, 4‐D and LPS. In conclusion, 2, 4‐D enhanced cell migration, promoted oxidative stress, induced excessive release of mitochondrial reactive oxygen species, promoted microglial cell activation, released inflammatory factors, activated NLRP3 inflammasomes, and inhibited autophagy. Meanwhile, LBP reduced inflammation and the release of mitochondrial reactive oxygen species, inhibited NLRP3 inflammasome activation, and regulated autophagy, thereby playing a neuroprotective role.